Analysis of the Crime of Buying and Selling Narcotics Class I As an Intermediary (Decision Study No. 1123/Pid.Sus/2025/PN Mdn) - ., Maswandi; Sitorus, Nanang Tomi; Sitompul, Ariman; Munthe, Riswan; Kartika, Arie (Journal of Cultural Analysis and Social Change, 2025)
This paper discusses the crime of Narcotics Group I with the status as an intermediary which is one form of crime that gets serious attention in Indonesia. Article 114 paragraph (1) of Law No. 35 of 2009 on narcotics expressly prohibits the sale, purchase, or intermediary in narcotics transactions of Class I. This article examines decision number 1123 / Pid.Sus / 2025 / PN Mdn who sentenced the defendant Benny Tanjung als Beny because he was legally and convincingly proven to have committed a criminal offense to be an intermediary in the sale and purchase of methamphetamine. This study uses a normative juridical approach by examining the law, doctrine, and analysis of court decisions. The results showed that the judge's consideration was in accordance with the elements of the article charged, by imposing a prison sentence of 7 years and a fine of Rp1, 000, 000, 000. This ruling affirms the consistency of the judiciary in supporting narcotics eradication policies, although it raises a discourse related to the proportionality of sanctions for intermediaries on a small scale.